SALURAN DAN MARGIN PEMASARAN DURIAN HASIL AGROFORESTRI DI DESA SIDODADI - Ari Yudha Prasetya; Rommy Qurniati; Susni Herwanti (Forestry Study Program University Of Mataram, 2020)
Durian is a plant that has high production potential planted by farmers in Sidodadi Village with agroforestry patterns. This production potential can provide benefits for farmers if they are able to be marketed efficiently. The purpose of this study was to analyze the channels and margins of durian marketing in Sidodadi Village, Teluk Pandan District, Pesawaran District, Lampung Province. The study was conducted in January 2019 with the object of research by farmers and durian marketing institutions in Sidodadi Village. Analysis was carried out qualitatively to assess marketing channels and quantitatively to calculate marketing margins. The results showed that marketing of durian in Sidodadi Village consisted of 3 marketing channels and led to the oligopsonistic market structure. The uneven value of marketing margins, profits, and farmer shares has caused the marketing system to be inefficient.